Changes in the Fermentation and Bacterial Community by Artificial Saliva pH in RUSITEC System - Guo, Tongqing; Guo, Tao; Cao, Yurong; Guo, Long; Li, Fei; Li, Fadi; Yang, Guo (Frontiers in Nutrition, 2021)
The purpose of the study was to assess the artificial saliva (AS) pH on ruminal fermentation and rumen bacteria community in the rumen simulation technique (RUSITEC) system. The experiment was performed in two treatments (low AS pH vs. high AS pH) with four replicates. The low AS pH was sustained by altering the composition of the AS (NaHCO3 from 9.8 to 1.96 g/L, Na2HPO4 from 9.3 to 1.86 g/L) according to McDougall's method. The diets were supplemented with 16 g basic diets with forage to the concentrate ratio of 50:50. The experiments were conducted over 13-day incubation periods, with 9 days adaption and 4 days sample collection. The results showed low AS pH decreased dry matter (DM) degradability (64.37 vs. 58.67%), organic matter (OM) degradability (64.38 vs. 59.32%), neutral detergent fiber (NDF) degradability (46.87 vs. 39.94%), acid detergent fiber (ADF) degradability (38.16 vs. 31.13%), and crude protein (CP) degradability (70.33 vs. 62.99%), respectively. Compared with the high AS pH, the low AS pH increased the proportion of butyrate (P = 0.008) and decreased the proportion of propionate (P < 0.001). At the bacteria community, the low AS pH increased the abundances of Spirochaetes (P = 0.001) and Synergistetes (P = 0.004) and decreased the Verrucomicrobia abundance (P = 0.004) in solid-associated bacteria. At the genus level, the low AS pH increased the abundance of Lactobacillus (P = 0.050) and decreased the abundance of Schwartzia (P = 0.002) in solid-associated bacteria. The abundances of Prevotellaceae_YAB2003_group (P = 0.040), Schwartzia (P = 0.002), and Ruminobacter (P = 0.043) were lower in the low AS pH group compared with the high AS pH group in liquid-associated bacteria. Low AS pH decreased the number of Ruminococcus albus, Ruminococcus flavefaciens, Fibrobacter succinogenes (P < 0.001) both in the solid- and liquid-associated bacteria, respectively. The results of the present study included three groups of bacteria communities according to the different sensitives to rumen pH: the abundances of Lactobacillus, Succinivibrio, and Prevotella_7 are increased with decreasing AS pH; the amounts of R. albus, R. flavefaciens, F. succinogenes as well as the abundances of Schwartzia and Ruminobacter decreased with the reducing AS pH; the abundances of Selenomonas_1, Rikenellaceae_RC9_gut_group, and Succiniclasticum were not affected by the AS pH in RUSTITEC.